Cultural and Linguistic Challenges in Pain Assessment: Rethinking Semantic Questionnaires for Rehabilitation Settings - Roberto Casale; Kestutis Petrikonis; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Semantic pain questionnaires, translated and validated in different languages from the original English version, are widely used to collect patient self-reports. Their use present significant challenges, as pain is a deeply personal experience influenced by individual, cultural, and linguistic factors, making it difficult to achieve consistent interpretation across diverse populations and cultures. Pain questionnaires are effective in research with carefully selected participants but may be less reliable in everyday ‘real world’ rehabilitation settings. Patients from rural areas with limited education may describe their chronic back pain as "a heavy burden on my life," whereas patients exposed to medical terminology might say "I have persistent, dull, aching pain in my lower back." Despite similar pain, their descriptions highlight a gap shaped by cultural and educational backgrounds. In rehabilitation, awareness of these biases is particularly important. Improvement in patient interviews will increase our ability to treat pain and pain related disability. Keywords: Pain assessment, rehabilitation, questionnaires, cross-cultural validity, patient-reported outcomes